1998
DOI: 10.1109/34.709616
|View full text |Cite
|
Sign up to set email alerts
|

Optical font recognition using typographical features

Abstract: Abstract-A new statistical approach based on global typographical features is proposed to the widely neglected problem of font recognition. It aims at the identification of the typeface, weight, slope and size of the text from an image block without any knowledge of the content of that text. The recognition is based on a multivariate Bayesian classifier and operates on a given set of known fonts. The effectiveness of the adopted approach has been experimented on a set of 280 fonts. Font recognition accuracies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(96 citation statements)
references
References 8 publications
1
91
1
3
Order By: Relevance
“…Gabriele [11] and Zramdini & Ingold [12] studied the physical aspect of typography and found that it has an impact to the mind, which is also agreed by Rojas & Roast [13].…”
Section: Literature Reviewsupporting
confidence: 57%
“…Gabriele [11] and Zramdini & Ingold [12] studied the physical aspect of typography and found that it has an impact to the mind, which is also agreed by Rojas & Roast [13].…”
Section: Literature Reviewsupporting
confidence: 57%
“…The font classifier is then applied first to a test field, and its decision is used to select the appropriate character classifier [40,41,42,43]. The same idea can be applied to writer identification [44].…”
Section: Font Classificationmentioning
confidence: 99%
“…As shown in Figure 4, text line images are composed of three typographical zones: the ascender, the x height and the descender zones, which are delimited by four virtual horizontal lines, ascender, x height, base and descender lines [3]. The lowercases with ascenders that extend above the x height line are b, d, f, h, k, l, i, and t. They occupy the ascender and the x height zones.…”
Section: Typographical Zonesmentioning
confidence: 99%
“…From the vertical projection profile of a word image after the correction of skew angle, the typographical structure can be estimated. The analysis of the vertical projection profile shows that a word image has one of four types [4], Type I: The presence of all three zones, Type II: The presence of the ascender and the x height zones,…”
Section: Typographical Zonesmentioning
confidence: 99%
See 1 more Smart Citation